Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2008
DOI: 10.1099/mic.0.2008/017533-0
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of the signal transduction protein GlnJ with the cellular targets AmtB1, GlnE and GlnD in Rhodospirillum rubrum: dependence on manganese, 2-oxoglutarate and the ADP/ATP ratio

Abstract: The PII family of signal transduction proteins is widespread amongst the three domains of life, and its members have fundamental roles in the general control of nitrogen metabolism. These proteins exert their regulatory role by direct protein-protein interaction with a multitude of cellular targets. The interactions are dependent on the binding of metabolites such as ATP, ADP and 2-oxoglutarate (2-OG), and on whether or not the PII protein is modified. In the photosynthetic nitrogen-fixing bacterium Rhodospiri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
34
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(38 citation statements)
references
References 44 publications
4
34
0
Order By: Relevance
“…However, for regulation of AmtB-GlnK complex formation, the antagonistic effect of ADP on 2-OG binding also appears to be critical. Many authors have proposed that P II proteins can sense changes in adenylate charge (16,21,42,43 (40,44), and our data are consistent with this. Consequently, it remains to be established whether there is a common underlying physiological link between the ATP/ADP ratio and regulation of P II interactions with specific targets.…”
Section: Discussionsupporting
confidence: 82%
See 2 more Smart Citations
“…However, for regulation of AmtB-GlnK complex formation, the antagonistic effect of ADP on 2-OG binding also appears to be critical. Many authors have proposed that P II proteins can sense changes in adenylate charge (16,21,42,43 (40,44), and our data are consistent with this. Consequently, it remains to be established whether there is a common underlying physiological link between the ATP/ADP ratio and regulation of P II interactions with specific targets.…”
Section: Discussionsupporting
confidence: 82%
“…At high 2-OG and in the absence of AmtB, formation of the GlnK-ATP complex was favored compared with GlnK-ADP by 2.7 kcal/ mol, whereas at low 2-OG and in the presence of AmtB, the reciprocal situation pertained, with formation of the AmtBGlnK-ADP complex favored by 2.4 kcal/mol (Table 1). These data for E. coli GlnK are largely consistent with similar studies of ligand binding to E. coli GlnB, which was assessed using an alternative technique (16). GlnB also shows negative cooperativity of ATP binding and synergistic binding of ATP and 2-OG.…”
Section: -Og Atp and Adp Pools In A Glnasupporting
confidence: 77%
See 1 more Smart Citation
“…A number of authors also have proposed that in addition to sensing the cellular nitrogen-status, P II proteins may also act as sensors of cellular adenylate energy charge; that is, as monitors of the ATP:ADP ratio in the cell (13)(14)(15)(16)(17)(18). The majority of those studies report either the differential binding of ATP and ADP to P II proteins in vitro or the in vitro effects of ATP and ADP on interactions of P II proteins with a number of their targets.…”
Section: +mentioning
confidence: 99%
“…It was long considered that ATP could not play a regulatory role because its intracellular concentration is typically 1-5 mM, whereas the affinity of P II proteins for the nucleotide is in the micromole range (K d ∼50 μM) (11,12). However, the subsequent recognition that ADP is also a physiological effector (10) led to a reevaluation of the role of nucleotides, and a number of studies concluded that P II proteins might also act as sensors of cellular energy status, as reflected by fluctuations in the ATP/ADP ratio (13)(14)(15)(16)(17)(18).…”
mentioning
confidence: 99%